O Arranjo produtivo local da opala no município de Pedro II - PI como instrumento de desenvolvimento sustentável a partir da mineração - SOUSA JÚNIOR, Dilmo Vieira de (Universidade Federal do Pará, 2023)
Sustainable development is development capable of meeting the needs of the present generation without compromising the ability to meet the needs of future generations. It is progress that does not deplete resources for the future, seeking to maintain a balance between social, environmental and economic aspects. Local Productive Arrangements (APLs) are a set of economic, political and social agents located in the same territory, developing related economic activities and that present expressive links of production, interaction, cooperation and learning. Mining is considered by many to be one of the basic sectors of the economy, both for its decisive contribution to the well-being and improvement of the quality of life of present and future generations, and for the contribution it makes to the development of a just and balanced society. to the extent that it requires concrete actions aimed at sustainability from its members. The cooperative network project of the opal productive arrangement in the Pedro II-PI region, aims to increase productivity from mining and consolidate the opal productive chain through a comprehensive and cooperative approach. The general objective of this study is to analyze the factors that hinder the operation of the opal APL as an instrument of sustainable development in Pedro II - PI. The methodology to be used in this research will be of an interpretative qualitative nature and will be based on the methodology of case studies involving the triangulation of data obtained through observation, documentary research and field research that will be interpreted through content analysis.